2016
DOI: 10.1016/j.mam.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Glycan susceptibility factors in autism spectrum disorders

Abstract: Idiopathic autism spectrum disorders (ASDs) are neurodevelopmental disorders with unknown etiology. An estimated 1:68 children in the U.S. are diagnosed with ASDs, making these disorders a substantial public health issue. Recent advances in genome sequencing have identified numerous genetic variants across the ASD patient population. Many genetic variants identified occur in genes that encode glycosylated extracellular proteins (proteoglycans or glycoproteins) or enzymes involved in glycosylation (glycosyltran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 91 publications
1
35
0
Order By: Relevance
“…Further studies are warranted to explore the relationship of HS content and composition in synaptic biology not only in MPS disorders, but also in other neurodevelopmental and neurodegenerative disorders that have shared characteristics with MPS III32.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are warranted to explore the relationship of HS content and composition in synaptic biology not only in MPS disorders, but also in other neurodevelopmental and neurodegenerative disorders that have shared characteristics with MPS III32.…”
Section: Discussionmentioning
confidence: 99%
“…PGs have been implemented in other neurodevelopmental disorders and neurodegenerative diseases that affect broader patient populations, and whose etiologies remain unknown. Autism spectrum disorders (affecting 1 in 70 children), and Alzheimer's (1 of 8 adults of 65 years old and over) and Parkinson's (1 in 1000 adults) diseases have all been linked to abnormal glycan variants, including PGs . For example, mutations in a unique dual‐function glycosyltransferase, encoded by the LARGE gene, that synthesizes repeating disaccharides of xylose and glucuronic acid and can modify dystroglycan (previously identified as CRANIN ), affect dystroglycan's capacity for binding to other ECM components and have been identified in cases of noncomplex autism .…”
Section: Brain Pathogenesismentioning
confidence: 99%
“…Despite intense research efforts over the past decade, the etiology of idiopathic ASD is stil unknown whereas syndromic ASD is secondary to a primary condition caused by a single gene mutation, for example fragile X syndrome 2). Also, researchers suggested that the place alterations in developmental transcriptional regulation, brain growth, changes in the excitatory/inhibitory balance of the neural network, and abnormalities in neural plasticity might have a role in pathogenesis 3)…”
Section: Introductionmentioning
confidence: 99%